STUDY OF THE DINAKA PIPE DANCE OF THE PEDI PEOPLE IN SOUTH AFRICA - Chambers, Paul W. (International Library of African Music, 2018)
This article provides a description and musical analysis of the Pedi genre known as dinaka, as it is currently practised (2016) in the rural areas throughout the Limpopo province. The role of this music is examined along with the implications of learning and performing it as a cultural outsider. The construction, methods of tuning, and playing techniques of the pipes, drums, and other instruments associated with dinaka are discussed. The form and structure of the music are interpreted as well as the idioms of rhythm, melody, and dance repertoire which imbue the genre with a distinct sound. Common methods for creating improvisational variations among the instrumental and dance parts are explained. The connection of dinaka to styles of Pedi vocal music is examined along with the proverbial meanings of the songs with which these melodies and rhythms are associated. Transcriptions of the dance steps, pipe melodies and drum rhythms have been developed to provide a visual representation of the music. The aim is to provide a resource from which one can study and understand the many aspects of dinaka.
Keywords: Dance; Transcription; South Africa; Dinaka (Music); Pedi (Music); South African Music; Drumming; Pipe Ensembles; African Music